Study of the ascorbic acid accumulation in Thymus L. genus species of Ukraine flora - O. V. Mazulin; Ya. M. Steshenko; L. A. Fukleva; H. V. Mazulin (Zaporozhye State Medical University, 2024)
The Thymus L. genus species are extremely widespread in temperate countries and number up to 200 main wild plants, of which up to 50 have been identified in the modern Ukraine flora. Extracts from the official species of the Thymus L. genus are part of effective herbal preparations with pronounced anti-inflammatory, antimicrobial, and antioxidant activities. A promising direction of modern phytochemical research is the determination of the presence and accumulation of biologically active ascorbic acid in the herbs of widespread wild and cultivated species of the Thymus L. genus. The aim of the work is to determine the presence and accumulation of biologically active L-ascorbic acid in the herbs of four widespread wild and cultivated species of the Thymus L. genus of Ukraine flora using thin layer chromatography (TLC) and spectrophotometry methods during vegetation season. Materials and methods. The research used herbs of four widespread wild and cultivated species of the Thymus L. genus of Ukraine flora during the growing season (June - August 2023). The presence and quantitative content of ascorbic acid were determined by TLC on a "Biostep" CD 60 densitometer (Germany) and spectrophotometry on a "Lambda 365' device (USA). Results. TLC and spectrophotometry methods were used to determine the presence and quantitative content of ascorbic acid in the herbs of four widespread Thymus L. genus species of Ukraine flora during the growing season. Accumulation of the compound was higher during flowering of cultivated species than wild plants. For the herbs Thymus vulgaris L. up to 39.10 ± 3.88 mg%; Th. x citriodorus (Pers.) Schreb. var. "Silver Queen" up to 36.19 ± 3.59 mg%. Conclusions. Considering the results obtained by TLC and spectrophotometry methods, it can be concluded that the determination of ascorbic acid presence and content in the Thymus L. species genus herbs is appropriate for obtaining cosmetology preparations with pronounced anti-inflammatory, antioxidant, and regenerating activity for normal and problem skin.